Faktor-Faktor yang Mempengaruhi Pengambilan Keputusan Petani Melakukan Usahatani Jagung Hibrida (Zea Mays) di Desa Tungka Kecamatan Enrekang Kabupaten Enrekang - Salmia Salmia; Nurhapsa Nurhapsa; Nurhaedah Nurhaedah; Irninthya Nanda Pratami Irwan (Jurnal Agribis, 2023)
The purpose of this study was to determine whether the influence of land area, experience, age, income, production, and geography factors significantly or not on farmers' decisions in conducting corn farming in Tungka Village, Enrekang District, Enrekang Regency. This research was conducted in Tungka Village, Enrekang District, Enrekang Regency in June-August 2022. The research method used was a survey method. While the sampling method used is simple random sampling. Methods of data collection using observation, documentation, and questionnaires. The data analysis used is quantitative descriptive analysis. There were 48 samples in this study which were processed using the SPSS 21 application and analyzed using multiple linear regression analysis techniques. From the results of the study, it is known: that the decision of farmers in cultivating corn farming is partially influenced by factors of age (X3), income (X4), and topography (X6) while simultaneously the six independent factors namely large area of ??land, experience, age, income, production, and topography no real effect.